Respuesta :

The solution using correct step of substitution in the equation y=2x-1 4x+y=2 is x = 1/2 and y = 0

Simultaneous equation

y = 2x - 1

4x + y = 2

  • Substitute the value of y in equation (1) into (2)

4x + y = 2

4x + (2x - 1) = 2

4x + 2x - 1 = 2

6x - 1 = 2

6x = 2 + 1

6x = 3

x = 3/6

x = 1/2

  • substitute the value of x into equation (1)

y = 2x - 1

y = 2(1/2) - 1

= 2/2 - 1

= 1 - 1

y = 0

Learn more about simultaneous equation:

https://brainly.com/question/16863577

#SPJ1